SEDIMENTATION RATE, DILUTION, PRESERVATION AND TOTAL ORGANIC CARBON: SOME RESULTS OF A MODELLING STUDY - Tyson R.V. (My University, 2001)
A modelling exercise was undertaken to evaluate the positive (preservational) and negative (diluent) effects of sedimentation rate (SR) on the total organic carbon (TOC) content of marine sediments, and to use multiple regression analysis of modern data to predict TOC. Data presented show the predicted marine TOC using the carbon burial efficiency (BE) versus SR relationship of Betts and Holland (Betts, J.N., Holland, H.D., 1991. The oxygen content of ocean bottom waters, the burial efficiency of organic carbon, and the regulation of atmospheric oxygen. Palaeogeography, Palaeoclimatology, Palaeoecology (Global and Planetary Change Section 97, 5-18), calculated for a range of SR, water depths, primary productivities and four fixed BE values. The results suggest that the preservation effect of SR only enhances TOC at =<5 cmka in oxic regimes, after which dilution occurs if carbon supply is held constant. above 35 thereno appreciable difference toc regardless of whether the sea floor anoxic or not. below 10 a strong divergence and values. observedpositive correlations sr at>5 cm/ka are largely an artefact of including sites from shallower depths and/or higher productivities. Multiple regression analysis (MRA) of modern marine sediment data suggests that once re-scaled to allow for their non-linear effect, dissolved oxygen values may be a significant additional variable in determining the TOC, predicting an approximately 2.5-4.0 times higher TOC in anoxic facies compared with fully oxic ones (>4 ml/l dissolved oxygen), all other things being equal. The MRA also indicates a generally negative partial correlation between carbon delivery flux and BE in modern sediments, producing a significant moderating effect on the predicted TOC.
Keywords: TOC; SEDIMENTATION RATE; BURIAL EFFICIENCY; ANOXIA